Effects of penthiopyrad on the development and behaviour of zebrafish in early-life stages. (January 2019) - Qian, Le; Qi, Suzhen; Cao, Fangjie; Zhang, Jie; Li, Changping; Song, Min; Wang, Chengju
Abstract: The agricultural use of succinate dehydrogenase inhibitor (SDHI) fungicides has increased dramatically in the US and Europe. As the SDHI fungicides, boscalid, flutolanil and thifluzamide had been reported to induce a series of toxic effects on zebrafish. However, the toxic effects of penthiopyrad on zebrafish have not been reported yet. This study aimed to assess the acute toxicity of penthiopyrad to zebrafish in early-life stages and investigate behavioural response of larvae and the effects on lipid metabolism and pigmentation under sub-lethal exposure of penthiopyrad. Based on results of the acute toxicity tests of zebrafish embryo and larvae, penthiopyrad had an acute toxicity to early-life stages of zebrafish and induced a series of deformities during development. Based on the results of sub-lethal exposure for 8 days, penthiopyrad resulted in significant decreases in swimming velocity, acceleration speed, distance moved and inactive time of larvae at 0.3, 0.6 and 1.2 mg/L. Penthiopyrad induced the disorders of lipid metabolism via affecting fatty acid synthesis and β- oxidation, in accordance with remarkable changes in the content of triglycerides and cholesterol and the expression of key genes ( hmgcrα, pparα1, srebf1, cyp51 and acca1 ) at 1.2 mg/L. In addition, the disorder of melanin synthesis and distribution was caused by penthiopyrad in larvae in accordance with changes in body colour and related gene expression at 8 dpe. Graphical abstract: Image 1 Highlights: Penthiopyrad has been widely used, but its toxicological assessment is lacking. Penthiopyrad had an acute toxicity to zebrafish in the early-life stages. Penthiopyrad induced a series of malformations in embryos and larvae. Penthiopyrad inhibited behaviours of larvae under sub-lethal exposure. Penthiopyrad caused the disorder of lipid metabolism and melanin deposition.